2008
DOI: 10.1002/eej.20723
|View full text |Cite
|
Sign up to set email alerts
|

A method of estimating the output fluctuation of many photovoltaic power generation systems dispersed in a wide area

Abstract: SUMMARYThe largest output fluctuation is an index used to quantify the disturbance of a power grid caused by wind power plants and photovoltaic power generation systems connected to it. In order to develop its estimation method, we investigate the relationship between the largest output fluctuation and the standard deviation of a newly proposed random variable generated by differencing the output variation of photovoltaic power generation systems. Output fluctuation coefficients are defined and estimated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 3 publications
1
67
0
Order By: Relevance
“…On the other hand, as far as the study of power fluctuations is concerned, the number of studies made is even more limited. The literature available only includes measurements with a 5 minute resolution on 100 PV systems (243 kWp in total) in Germany [5]; data taken at 10 second and 1 minute intervals at a fixed 4.6 MWp system and measurements taken every 10 minutes at three 100 kWp plants in Arizona (USA) [6] and, finally, data recorded with a one minute resolution over a 3 month period on 52 PV systems in Japan, with an approximate mean power per system of 3.2 kWp [7].…”
Section: Experimental Set-upmentioning
confidence: 99%
“…On the other hand, as far as the study of power fluctuations is concerned, the number of studies made is even more limited. The literature available only includes measurements with a 5 minute resolution on 100 PV systems (243 kWp in total) in Germany [5]; data taken at 10 second and 1 minute intervals at a fixed 4.6 MWp system and measurements taken every 10 minutes at three 100 kWp plants in Arizona (USA) [6] and, finally, data recorded with a one minute resolution over a 3 month period on 52 PV systems in Japan, with an approximate mean power per system of 3.2 kWp [7].…”
Section: Experimental Set-upmentioning
confidence: 99%
“…As a consequence, each plant compensates the fluctuations occurred in another plant separated by sufficient distance. In (Murata and Otani, 1997;Murata et al, 2009), simulated and measured PV power data are used for analysing the smoothing effect of distributing a large number of PV plants along a country-level region. They obtained a correlation between output power fluctuations and the distances between the locations of the plants.…”
Section: Methods To Mitigate Pv Power Fluctuationsmentioning
confidence: 99%
“…In previous works, procedures have been proposed to characterise PV power fluctuations and to size batteries for complying with a certain power ramp rate limitation. Despite part of the fluctuations can be smoothed by geographically dispersing PV plants (Lave et al, 2012;Marcos et al, 2012;Murata et al, 2009), strict grid regulations demand buffering capabilities to individual PV plants. By analysing PV powers fluctuations statistically, in (Perez and Hoff, 2013;van Haaren et al, 2015) the fluctuations mitigation is addressed by means of energy storage systems.…”
Section: Chapter 3 Sizing Of Batteries Applied To Pv Power Fluctuatiomentioning
confidence: 99%
“…In 2009, Murata, Yamaguchi and Otani [34] investigated the geographic correlation between PV output fluctuations in different places in Japan and found that PV variability depends on the data recording interval and the physical distance between PV units. Larger distances and higher data resolution will result in lower variability correlation.…”
Section: Pv Variability Study In the Literaturementioning
confidence: 99%
“…Larger distances and higher data resolution will result in lower variability correlation. Hoff and Perez [35] and Mills and Wiser [36] in 2010 expanded the relationship developed by Murata, Yamaguchi and Otani [34] by including the number of PV systems and the dispersion factor, and formulating them into equations for PV output variability prediction.…”
Section: Pv Variability Study In the Literaturementioning
confidence: 99%